Tinjauan Perbedaan ICD-10 dan IC-10-CM - Nita Budiyanti; Diana Nafisah Noor; Lina Khasanah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The ICD (International Statistical Classification of Disease and Related Health Problems) provides a common language for classifying diseases, injuries and causes of death. The progress of the times affects the quality of data related to the classification system on the ICD-10. Since 1992, several countries have developed clinical modifications of ICD-10 to meet the specific needs of each country. The clinical modification of ICD-10 has the advantage of more detailed characterization of the patient's condition. The purpose of this study was to determine the differences in the basic structure of ICD-10 and ICD-10-CM. This study was a literature review. Based on the results of the study, there were differences in volume, namely three volumes on the ICD-10 and two volumes on the ICD-10-CM. The chapter differences are 22 chapters on ICD-10 and 21 chapters on ICD-10-CM. The category block differences are five characters on the ICD-10 and five to seven characters on the ICD-10-CM. Differences in punctuation conventions on ICD-10 and ICD-10-CM. The differences in the coding steps are eight coding steps on the ICD-10 and five coding steps on the ICD-10-CM. And no differences were found in the three and four character categories on ICD-10 and ICD-10-CM. The differences in volume, chapters, sub categories, punctuation conventions and coding steps on ICD-10 and ICD-10-CM were obtained. The suggestions given include: the role of professional organizations in increasing competence through socializing the latest updates on the ICD.Keywords: ICD-10 and ICD-10-CMABSTRAK ICD (International Statistical Classification of Disease and Related Health Problem) menyediakan bahasa umum untuk klasifikasi penyakit, cedera dan penyebab kematian. Kemajuan zaman mempengaruhi kualitas data terkait sistem klasifikasi pada ICD-10. Sejak tahun 1992, beberapa negara mengembangkan modifikasi klinis ICD-10 untuk memenuhi kebutuhan spesifik disetiap negaranya. Modifikasi klinis ICD-10 mempunyai kelebihan dalam karakterisasi lebih rinci dari keadaan pasien. Tujuan studi ini adalah mengetahui perbedaan struktur dasar ICD-10 dan ICD-10-CM. Studi ini merupakan literatur review. Berdasarkan hasil studi diperoleh perbedaan volume yaitu tiga volume pada ICD-10 dan dua volume pada ICD-10-CM. Perbedaan bab yaitu 22 bab pada ICD-10 dan 21 bab pada ICD-10-CM. Perbedaan blok kategori yaitu lima karakter pada ICD-10 dan lima hingga tujuh karakter pada ICD-10-CM. Perbedaan konvensi tanda baca pada ICD-10 dan ICD-10-CM. Perbedaan langkah pengkodean yaitu delapan langkah pengkodean pada ICD-10 dan lima langkah pengkodean pada ICD-10-CM. Serta tidak ditemukan perbedaan pada kategori tiga dan empat karakter pada ICD-10 dan ICD-10-CM. Diperoleh perbedaan volume, bab, sub kategori, konvensi tanda baca serta langkah pengkodean pada ICD-10 dan ICD-10-CM. Saran yang diberikan meliputi: peran organisasi profesi dalam peningkatan kompetensi melalui sosialisasi update terbaru mengenai ICD.Kata Kunci: ICD-10 dan ICD-10-CM